Notary Authority in the Making of Minutes Deed of Electronic General Meeting of Shareholders (E-GMS) For Public Company based on the Principle of Legal Certainty - Rizky Olvia, Ghea; Saprudin, Saprudin (Program Studi Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2024)
This research analyzes the authority of notaries in creating minutes deeds for e-GMS of Public Companies, based on the principle of legal certainty. The research uses normative juridical methods, employing a conceptual approach to laws, regulations, theories, and expert opinions to address the issues raised. The findings indicate that the stipulations in article 12 of POJK 16/2020, which require that e-GMS minutes be made in the form of a notarial deed without signatures from the GMS participants, align with article 46 of UU-JN. This alignment provides legal certainty regarding the Notary's authority in conducting e-GMS. Despite conflicts between POJK 16/2020 and UU-PT, POJK 16/2020 is considered a specific provision (lex specialis) through UU-4/2023, while UU-PT is a general provision (lex generalis). Article 8 paragraph (1) letter b of POJK 16/2020 aligns with article 16 paragraph (1) of UUJN-P, emphasizing the necessity of physical presence for notaries, appearing parties, and witnesses in notarial deeds. Without clear